Time and reglamentary analysis during high level wheelchair basketball competition: training conclusions - Pérez-Tejero, J.; Pinilla-Arbex, J.; Aceituno-Duque, J.; Sampedro-Molinevo, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
One of the key factors while determining physical effort in a collective sport is the analysis of the duration of game actions, reglamentary pauses and their origin. Therefore, the aim of this study was to analyze the incidence of the game and pause phases in wheelchair basketball, as well as the duration and frequency of events triggering those pauses. A systematic observation was carried using an ad hoc observational instrument on a total of 24 high level WB matches, where 17 teams participated. 56959 s were analyzed, with an average of 4773±567 s per game, distributed in 80.5±14.2 game action phases and 77±14.7 pause phases, being their duration 29±25 s and 30±39 s, respectively. 47,1% of game situations took less than 20 s and just the 11,8% took more than 60 s. The 50,1 % of the pause phases were shorter than 20 s and just the 9,9% was superior to 60 s. Personal faults and out of bounds were the regulation incidences which developed more pause phases (85,4% of the total). These data provide crucial information to the coaches to frame physical training in order to replicate sport specific exigency of elite wheelchair basketball.